PENGARUH KINERJA KEUANGAN DAN MEKANISME CORPORATE GOVERNANCE TERHADAP FINANCIAL DISTRESS (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2011-2014) - Anis Mafiroh; Triyono Triyono (Riset Akuntansi dan Keuangan Indonesia, 2016)
Financial distress is the financial difficulties experienced by a company before the company become bankruptcy. The prediction of financial distress is necessary to anticipate a company into bankruptcy. While the company showed the signal will be bankruptcy, show the parties concerned such as managers, investors, and business owners will soon take a decision anticipated for bankcruptcy. Financial ratios in this study using indicators such as leverage ratio, liquidity ratios, activity ratios, profitability ratios, independent board and audit committee competence on a predicted occurrence of Financial distress.The population in this study was all manufacturing companies listed in Indonesia stock exchange and continuosly published financial statement in the periode 2011-2014. The sample is determined by purposive sampling technique and used of 79 companies as samples. This analysis used logistic regression analysis. The result of this research showed that the leverage ratio and the ratio of activity affect the prediction of the occurrence of financial distress, while liquidity ratios, profitability ratios, independent board, and the competence of the audit committee do not affect the prediction of financial distress.